Detection of ovine antibody to Brucella ovis by Indirect Enzyme Immunoassay - Nielsen, Klaus; Smith, P.; Yu, W. L.; Rojas, X.; Perez, B.; Conde, Sandra Beatriz; Samartino, Luis Ernesto; Robles, Carlos Alejandro (Taylor & Francis Group, 2022)
Because some batch-to-batch variation in the preparation of rough lipopolysaccharide (RLPS) from Brucella ovis has been experienced, several protocols were tested to establish the most reliable method for detection of antibody in indirect enzyme immunoassay. An early version of the assay gave a performance index (PI ¼ sum of optimum percent sensitivity and percent specificity, determined by receiver operator characteristic analysis) of 198.6. This assay used RLPS from B. ovis as the antigen and a monoclonal antibody specific for bovine IgG1 heavy chain-enzyme conjugate for detection. This was not repeatable using other batches of antigen. Newer versions of the assay generally had decreased sensitivity values, giving PIs of 193. Use of a recombinant protein A/G-enzyme conjugate did not improve the PI (PI ¼ 190), giving reduced specificity and higher sensitivity. The final version used B. abortus RB51 RLPS as the antigen and protein A/G-enzyme conjugate for detection, giving a PI of 197. Because of the batch uniformity of the B. abortus RB51 RLPS and the versatility of the protein A/G-enzyme conjugate, the latter version appears to be the most useful for diagnostic serology.